2014
DOI: 10.1038/tpj.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NEGR1 genetic variability on psychological traits of patients with eating disorders

Abstract: Genetics variants in the NEGR1 gene, strongly expressed in the brain, have been reported to affect the neuronal control of food intake therefore inducing obesity. With the same rationale, we hypothesized that this genetic variability may be associated with psychological traits commonly displayed by eating disorder (ED) patients and/or with the risk for the disorder. We analyzed 21 tag-single-nucleotide polymorphisms (SNPs) in the coding sequence and adjacent regions of the NEGR1 gene. A total of 169 ED patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…With regard to its role in ED, Brandys et al analyzed the effect of NEGR1 rs2568958 on AN risk, without finding evidence for this association [127], which is in line with our results in AN and BN patients [148]. However, in this last study, we also performed a combined analysis of 21 tag-SNPs of NEGR1 in relation to a variety personality dimensions in the patients.…”
Section: Neuronal Growth Regulatorsupporting
confidence: 91%
See 1 more Smart Citation
“…With regard to its role in ED, Brandys et al analyzed the effect of NEGR1 rs2568958 on AN risk, without finding evidence for this association [127], which is in line with our results in AN and BN patients [148]. However, in this last study, we also performed a combined analysis of 21 tag-SNPs of NEGR1 in relation to a variety personality dimensions in the patients.…”
Section: Neuronal Growth Regulatorsupporting
confidence: 91%
“…However, in this last study, we also performed a combined analysis of 21 tag-SNPs of NEGR1 in relation to a variety personality dimensions in the patients. Interestingly, haplotype analyses and a sliding-window approach identified a central region of the gene spanning 210 kb whose variability strongly correlated with higher scores of BN patients in drive for thinness, ineffectiveness and interoceptive awareness [148].…”
Section: Neuronal Growth Regulatormentioning
confidence: 99%
“…For the multiple‐marker analysis, the p ‐value was adjusted by the number of haplotypes identified in the population. The number of psychopathological scales analyzed was not included in the adjustment, as previous studies in ED patients have claimed this would be too stringent to detect moderate associations with different endophenotypes (Gamero‐Villarroel et al., 2014, 2015; Mercader et al., 2007). Haplotype associations were performed with the haplo.stats package, also in the R environment.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, we and others have shown that variability in these genes is also associated with ED‐related behaviors (Gamero‐Villarroel et al., 2014, 2015; Muller et al., 2012; Rybakowski et al., 2007). According to this background, we hypothesized in the present work that TFAP2B and KCTD15 variants, either isolated or in combination, may influence personality dimensions in anorexia nervosa (AN) or bulimia nervosa (BN) patients.…”
Section: Introductionmentioning
confidence: 99%
“…This claim is supported by genetic studies which suggest that self-report deficits in interoceptive awareness may contribute to the development of eating disorders (Frieling et al, 2006; Gamero-Villarroel et al, 2015), findings from a self-report study that indicates that interoceptive awareness deficits are found in teenage girls who later develop eating disorder symptoms (Leon et al, 1993) and findings from studies that examine women recovered from BN. Deficits present after recovery may indicate either that interoceptive deficits existed prior to the development of an eating disorder or that interoceptive deficits are a scar from having BN.…”
Section: Discussionmentioning
confidence: 84%